Stability analysis of the reference standard of Mycoplasma arginini strain G230 used for testing biologicals for mycoplasmas - S. M. Sukhanova; Z. E. Berdnikova; O. V. Fadeikina; E. M. Petruchuk; A. S. Tikhonova (Биопрепараты: Профилактика, диагностика, лечение, 2022)
The State Pharmacopoeia of the Russian Federation (Ph.Rus.) requires a preparatory evaluation of culture medium suitability using the reference standard (RS) of the Mycoplasma arginini G230 test strain in order to ensure reliable results when testing medicines for mycoplasmas using a microbiological (culture) method. The RS retains the stability of physico-chemical properties and the certified characteristic value (titre) for one year if stored under the specified temperature conditions (–20 ºC to –30 ºC). Deviations from this range and transportation in ambient conditions can alter the properties of the RS and consequently result in biologicals substandard in terms of mycoplasmas. Experts from the Reference Materials Committee of the International Organisation for Standardisation (ISO), the State System for Ensuring the Uniformity of Measurements, and the WHO Expert Committee on Biological Standardisation emphasise the need to study the stability of RSs not only under the specified long-term storage conditions, but also with short-term deviations from such conditions. The aim of the study was to analyse the stability of the M. arginini G230 test strain RS under the specified long-term storage conditions and with short-term exposure to elevated temperatures. Materials and methods: the study used the RS of M. arginini G230 by the Scientific Centre for Expert Evaluation of Medicinal Products and culture media and solutions required per the Ph.Rus. general chapter on mycoplasma tests (OFS.1.7.2.0031.15). The stability of RS’s characteristics, including the certified value (titre), was determined using Ph.Rus. methods. The experiment involved two testing regimes with short-term exposure to elevated temperatures. Control samples were stored at –20±2 °С. Statistical data processing was carried out by the serial dilution method using McCrady’s table with the calculation of the arithmetic mean of the most probable number (MPN) for the limiting dilution (titre). Results: as demonstrated in the study under the specified conditions, the RS retains its characteristics for a period exceeding its shelf life (for up to 16 months). The main characteristics of the RS remain stable after 30-day exposure to elevated temperatures (25±2 ºC and 37±2 ºC). The certified value (titre) of the RS decreases after exposure to 37±2 ºC for 10 and 30 days. Conclusions: the study proved the possibility of storing and transporting the RS at a temperature lower than 25±2 ºC for up to 30 days with no subsequent changes to the quality within the 1-year shelf life. The conditions of 37±2 ºC cannot be used for the purpose.